Optimizing the contribution of cowpea to food and fodder production in croplivestock systems in West Africa - Tarawali, Shirley A.; Singh, B.B.; Fernández Rivera, S.; Peters, M.; Smith, J.W.; Schultze-Kraft, Rainer; Ajeigbe, Hakeem A. (Canadian Forage Council, 1997)
Cowpea is important for the provision of both grain for food and fodder for livestock but there is often a trade-off between productions of two. To better understanding influences on grain and fodder production, and how these may be influences on grain and fodder production, and two these may be utilized, research was conducted at 5 location in west Africa using 12 cowpea varieties, with and without insecticide spray. Spraying had a dramatic effect on grain production, but less so for fodder, however there was an effect of spraying on fodder quality in term of insacco digestibility at Niamey. Accessions with the potential to produce grain and fodder with good quality were identified (IT89KD-39I and TVU 12349) and studies are continuing to optimize the contribution of such material to local production systems